USING SCRABBLE FOR LEARNING ENGLISH VOCABULARY AT MAN 2 KUANTAN SINGINGI - Sri Chairani (Universitas Islam Sumatera Utara (UISU), 2021)
Reading, writing, listening, and speaking are four language skills that need to be mastered. The skills include language components: vocabulary, grammar, spelling, and pronounciation. Among the language components, vocabulary become potential to be improved with various medias of learning since vocabulary is one of the main factors to understand a language. Therefore, this research is determined to find out the impacts of using scrabble for learning English vocabulary at Kampung Inggris Pare AEC MAN 2 Kuantan Singingi. The scrabble game can help the students understand vocabulary easily. They have to arrange words using the given letter tiles onto the board game. The method used to do this analysis is qualitative research method due to its suitability for generating the data properly. The result of this research shows that scrabble does not only improve the motivation and interest, but also students’ vocabulary mastery in term of spelling, pronouncing and memorizing of vocabulary, and also gives much contribution to their speaking ability as well. The class can be more enjoyable, and furthermore, such class can make the students enthusiastic and confident to speak English.